PENDEKATAN STRUKTURALISME DALAM PENELITIANN SASTRA, BAHASA, DAN BUDAYA - Kasno Atmo Sukarto (Pujangga: Jurnal Bahasa dan Sastra, 2017)
Structuralism approach can be applied in language, literary and culture research. The research aims at describing Structuralism approach in language, literary and culture research. Structuralism is generally a doctrine or method that considers its object is not just the only one a collection of separate elements, but rather as a combination of elements that are related to one another, so that one depends on the other. Research method of this research is analysis descriptive. In this research, the researcher found description of structuralism relates with intrinsic literary object, language structure associated with form, category, function and role. Intrinsic culture associated with its local wisdom of society covered attitude, value, state of mind and how to work.